Factors Affecting Investment Decision in Nepalese Stock Market - Dasuni, Prem Bhadur (The Gaze: Journal of Tourism and Hospitality, 2024)
The Nepalese stock market has grown significantly, attracting domestic and international investors. However, various behavioral and psychological factors that impact investor behavior and market efficiency influence investment decisions in this market. This study aims to identify and analyze these factors, providing critical insights for investors and policymakers. Three hundred eighty-eight active investors in the Nepalese stock market, aged 18–44, participated in the study, completing structured electronic questionnaires. The study adopted a causal-comparative research design to explore the effects of trait anger, trait anxiety, overconfidence, herding effect, and self-monitoring on investment decisions. The findings reveal that trait anger significantly influences investment decisions, with higher levels of anger associated with poor decision-making. Conversely, trait anxiety showed no significant effect on investment decisions. Overconfidence was found to have a positive impact, leading to improved investment choices, while the herding effect also demonstrated a beneficial influence on decision-making. However, self-monitoring had no significant effect on investment decisions. The implications of these findings suggest that behavioral biases, such as anger and overconfidence, can drive impulsive and risky decisions, while anxiety may contribute to financial inertia. Understanding these psychological factors can help investors make more informed decisions, while policymakers and financial advisors can use these insights to foster better market practices and improve investor outcomes.